Endoscopic submucosal dissection for superficial esophageal neoplasms using the stag beetle knife. Issue 1 (26th February 2013) - Fujinami, H.; Hosokawa, A.; Ogawa, K.; Nishikawa, J.; Kajiura, S.; Ando, T.; Ueda, A.; Yoshita, H.; Sugiyama, T.
Summary Endoscopic submucosal dissection (ESD) is an accepted standard treatment for early gastric cancer but is not widely used in the esophagus because of technical difficulties. To increase the safety of esophageal ESD, we used a scissors‐type device called the stag beetle (SB) knife. The aim of this study was to determine the efficacy and safety of ESD using the SB knife. We performed a single‐center retrospective, uncontrolled trial. A total of 38 lesions were excised by ESD from 35 consecutive patients who were retrospectively divided into the following two groups according to the type of knife used to perform ESD: the hook knife (hook group) was used in 20 patients (21 lesions), and the SB knife (SB group) was used in 15 patients (17 lesions). We evaluated and compared the operative time, lesion size, en bloc resection rate, pathological margins free rate, and complication rate in both groups. The operative time was shorter in the SB group (median 70.0 minutes [interquartile range, 47.5–87.0]) than in the hook group (92.0 minutes [interquartile range, 63.0–114.0]) (P = 0.019), and the rate of complications in the SB group was 0% compared with 45.0% in the hook group (P = 0.004). However, the lesion size, en bloc resection rate, and pathological margins free rate did not differ significantly between the two groups. In conclusion, ESD using the SB knife was safer than that using a conventional knife for superficial esophageal neoplasms.